PROFESSIONAL COMMUNICATION IN A FOREIGN LANGUAGE: EXPERIENCE IN DESIGNING THE CURRICULUM FOR 024 CHOREOGRAPHY SPECIALTY - Yuliia Rudnik (Неперервна професійна освіта: теорія та практика)
The article is devoted to the problem of the designing of the discipline «Professional Communication in a Foreign Language» working curriculum for the preparation of 024 Choreography specialty students. The designing of a working curriculum is one of the most important aspects in the process of planning in terms of the professional training of each specialty. The necessity of its review and updating on the yearly basis is proved in the article. The goal and aims of the discipline «Professional Communication in a Foreign Language» are based on the program of education and professional training for the students of the second level of higher education (Master) 024.00.01 «Choreography» are presented by the author. For instance, the need for the development of the competencies that allow communicating with the representatives of the other professional groups is granted by the content. The expected learning outcomes for 024 Choreography specialty students are discussed. The used references for the course design are reviewed. The structure of the working curriculum as well as its integration with the certified course for distance learning on the Moodle e-learning platform has been described in the article below. The results of students’ questionnaires based on the completion of the discipline «Professional Communication in a Foreign Language» course are revealed and discussed. The further transformations of the working curriculum and the place for the next research are emphasized.